USE GREETINGS OF PARENTS' NAMES AS SOCIAL IDENTITY OF STUDENTS OF STATE SENIOR HIGH SCHOOL 16 SAMARINDA : A SOCIOLINGUISTIC STUDY - Sri Hadijati; Syamsul Rijal; Masrur (RADJA PUBLIKA, 2026)
Study This study use greeting based on parents ' names in interaction daily students of State Senior High School 16 Samarinda as practice language that represents identity social teenagers . Research This use approach qualitative descriptive with method ethnography communication . Data obtained through observation participatory , interview deep to students and teachers, as well as documentation speech in context informal interactions in the environment school . Research result show that use parents ' names form three pattern main , namely (1) greeting identification as marker introduction individual in group peers , (2) greetings humorous as a building strategy solidarity and familiarity social , and (3) greetings functional evaluative​ as satire light within the boundaries of the relationship friendship . Practice greeting the reflect construction identity social negotiated students​ through proximity relationship , context situational , and objective communication . From the perspective politeness speaking , greeting humorous functioning as a positive politeness strategy, whereas greeting evaluative potential becomes a face-threatening act if used outside​ context familiarity . Research This confirm that use greetings among​ high school students do not nature neutral , but rather play a role as symbol identity social and dynamics relation in community school .